A Guide to Posting and Managing Preprints. Issue 2 (June 2021) - Moshontz, Hannah; Binion, Grace; Walton, Haley; Brown, Benjamin T.; Syed, Moin
Posting preprints online allows psychological scientists to get feedback, speed dissemination, and ensure public access to their work. This guide is designed to help psychological scientists post preprints and manage them across the publication pipeline. We review terminology, provide a historical and legal overview of preprints, and give guidance on posting and managing preprints before, during, or after the peer-review process to achieve different aims (e.g., get feedback, speed dissemination, achieve open access). We offer concrete recommendations to authors, such as post preprints that are complete and carefully proofread; post preprints in a dedicated preprint server that assigns DOIs, provides editable metadata, is indexed by GoogleScholar, supports review and endorsements, and supports version control; include a draft date and information about the paper's status on the cover page; license preprints with CC BY licenses that permit public use with attribution; and keep preprints up to date after major revisions. Although our focus is on preprints (unpublished versions of a work), we also offer information relevant to postprints (author-formatted, post-peer-review versions of a work) and work that will not otherwise be published (e.g., theses and dissertations).